Modifikasi Sistem Asistensi dan Responsi Kelas Kecil pada Praktikum Parasitologi Blok Digestif dan Hematoimunologi Fakultas Kedokteran Universitas Riau - Suri Dwi Lesmana; Esy Maryanti (Fakultas Kedokteran Universitas Riau, 2014)
Faculty of Medicine University of Riau has been implementing Competency Based Curriculum (KBK) with theProblem Based Learning (PBL) since 2007 with the implementation of teaching and learning activities of the systemconsists of a tutorial activities, skillab, expert lectures, independent and practical. However, there are still manyproblems in the implementation of the KBK on preclinic degree. One part of the block that is identified to be one ofthe causes of low graduation exam block is less efective coaching laboratory practice. Parasitology is one part of thetask is to provide laboratory practice in several blocks on the stage of preclinic especially digestive and hematoimunologyblock. This study aimed to compare the results of the evaluation of parasitology laboratory practice in hematoimunologyand digestive assistance and posttest in large classes with small class. Assistance and posttest in large class performedon the digestive block implementation and hematoimunologi in 2011 while assisting and posttest of small classes ona block implementation in 2012. Average value of small class digestive laboratory practice was not significantlylower than the large class but the proportion of the value of quality B and C more many in small classes. The meanvalue of the block hematoimunologi laboratory practice significantly higher on small class assistance and posttest aswell as the proportion of the value of quality A, B and C was higher in small classes than large classes.